From painful places to commemorative landscapes: Utøya in Norway. Issue 1 (2nd January 2017) - Dietze-Schirdewahn, Annegreth
Abstract: Landscape can play a powerful role in commemorative sites, but this role is often neglected. In Norway, an important discussion about commemorative sites started because of the significant events that took place in July 2011: the bombing of the Government Headquarters in Oslo and the subsequent massacre on Utøya island. This article contributes to the discussion from a landscape architectural perspective. It links cases from recent history in Norway to the current development of Utøya. Commemorative sites are related to collective memory and are therefore dependent on local culture and identity. The historical cases reflect the significance of landscapes, and show different options for development over time in the processes of creating commemorative landscapes. A broader landscape approach differs from the thinking with respect to traditional monuments. It is essential to allow time to pass: with a longer time horizon, the commemorative site leads from a painful moment to historical experiences.